Definition of the Lithuanian Judicial Council - Borusevičiūtė, Miranda (Teisė, 2023)
The paper analyzes the institution of judges – the Lithuanian Judicial Council referred to in Article 112(5) of the Constitution of the Republic of Lithuania. The paper attempts to define this institution by considering various alternatives of interpretation of the Constitution of the Republic of Lithuania and at the same time assessing the interpretation of this document made by the Constitutional Court of the Republic of Lithuania.